TiO2-Photocatalyzed degradation of phenol in saline media in an annular reactor: hydrodynamics, lumped kinetics, intermediates, and acute toxicity - Azevedo,E. B. (2009)
The photocatalytic degradation of phenol in aqueous suspensions of TiO2 under different salt concentrations in an annular reactor has been investigated. In all cases, complete removal of phenol and mineralization degrees above 90% were achieved. The reactor operational parameters were optimized and its hydrodynamics characterized in order to couple mass balance equations with kinetic ones. The photodegradation of the organics followed a Langmuir-Hinshelwood-Hougen-Watson lumped kinetics. From GC/MS analyses, several intermediates formed during oxidation have been identified. The main ones were catechol, hydroquinone, and 3-phenyl-2-propenal, in this order. The formation of negligible concentrations of 4-chlorophenol was observed only in high salinity medium. Acute toxicity was determined by using Artemia sp. as the test organism, which indicated that intermediate products were all less toxic than phenol and a significant abatement of the overall toxicity was accomplished, regardless of the salt concentration.